The Impact of Macroeconomic Factor to Household Debt in Malaysia: A Theoretical Framework - Yahaya, S.N.; Sarwe, N.A. (International Journal of Human and Technology Interaction (IJHaTI), 2019)
Malaysia household debt is keep on increasing year to year, even though the economic condition shows the unstable performance. Therefore, this study attempts to study how macroeconomics factor impact to household debt. Considering both mortgage and consumer debt hence the study will add more reference to analyst in analyzing the debt offered to the consumer. The study used 10 years period from 2008 to 2017. Five variables are determined to be included in this study include gross domestic product (GDP), interest rate (IR), house price index (HPI), Unemployment Rate (UNEM), and consumer price index (CPI). The relationship of macroeconomic performance and housedebt will be tested using multiple regression models. Secondary data from reliable sources will be gathered